Atomic real-space perspective of light-field-driven currents in graphene. (1st March 2022) - Morimoto, Yuya; Shinohara, Yasushi; Ishikawa, Kenichi L; Hommelhoff, Peter
Abstract: When graphene is exposed to a strong few-cycle optical field, a directional electric current can be induced depending on the carrier-envelope phase of the field. This phenomenon has successfully been explained by the charge dynamics in reciprocal space, namely an asymmetry in the conduction band population left after the laser excitation. However, the corresponding real-space perspective has not been explored so far although it could yield knowledge about the atomic origin of the macroscopic currents. In this work, by adapting the nearest-neighbor tight-binding model including overlap integrals and the semiconductor Bloch equation, we reveal the spatial distributions of the light-field-driven currents on the atomic scale and show how they are related to the light-induced changes of charge densities. The atomic-scale currents flow dominantly through the network of the π bonds and are the strongest at the bonds parallel to the field polarization, where an increase of the charge density is observed. The real-space maps of the currents and changes in charge densities are elucidated using simple symmetries connecting real and reciprocal space. We also discuss the strong-field-driven Rabi oscillations appearing in the atomic-scale charge densities. This work highlights the importance of real-space measurements and stimulates future time-resolved atomic-scale experimental studies with high-energy electrons or x-rays, for examples.